Factors Influencing Early Childhood Development Teachers' Motivation in Thika District, Kenya - Mary N. Ndani; Elishiba N Kimani (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2011)
Early Childhood Development (ECD) centres comprise one of the immediate social and physical environments influencing children's development, that Bronfenbrenner (1986, 1989) terms Microsystems. The Microsystems are made up of personal qualities of the people therein (particularly teachers) and the physical environments. In order for ECD centres to provide the necessary conditions for children's holistic development, teachers should be well motivated and physical facilities conducive for working and learning.  The sample of the study was comprised of 40 ECD centres and 46 ECD teachers. Preschool Teachers' Motivation Questionnaire and an observation checklist were used to collect the primary data. Secondary data were obtained from various records in the ECD centres. Among the key findings was the revelation that the motivation levels of more than 50% of the teachers were below average. The study recommended that the Ministry of Education and communities work together to improve ECD teachers' terms and conditions of service as well as the learning/teaching environment.